Correlation of Serum Level of Progesterone with Peak Expiratory Flow Rate (PEFR) in Different Phases of Menstrual Cycle (Anwer Khan Modern Medical College Journal, 2012)
The present study has been carried out to observe the correlation of endogenous serum progesterone level with PEFR during luteal and follicular phases of two consecutive menstrual cycles. This study was conducted on 30 healthy young female volunteers with age ranges of 20- 24 years in the Department of Physiology of Bangladesh Shikh Mujib Medical University (BSMMU), Dhaka during July, 2005 to June, 2006. Serum progesterone level and PEFR of all subjects during all three phases of menstrual cycles were measured by ELISA method and a portable Spirometer respectively. Plasma progesterone level is highest during luteal phase; which is about 24 fold higher than that at follicular phases. (24.54ng/ml vs 1.4ng/ml). PEFR was positively correlated with progesterone level, but statistically not significant and it was significantly higher during luteal phase than follicular phase. This result indicates that changes in the pulmonary function occurred during different phases of menstrual cycle and this is more marked during luteal phase. DOI: http://dx.doi.org/10.3329/akmmcj.v3i1.10105 AKMMCJ 2012; 3(1): 6-9